2013
DOI: 10.1002/mc.22038
|View full text |Cite
|
Sign up to set email alerts
|

TPD52 represents a survival factor inERBB2‐amplified breast cancer cells

Abstract: TPD52 and ERBB2 co-expression has been persistently reported in human breast cancer and animal models of this disease, but the significance of this is unknown. We identified significant positive associations between relative TPD52 and ERBB2 transcript levels in human diagnostic breast cancer samples, and maximal TPD52 expression in the hormone receptor (HR)- and ERBB2-positive sub-group. High-level TPD52 expression was associated with significantly reduced metastasis-free survival, within the overall cohort (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 46 publications
4
38
0
Order By: Relevance
“…MTT assays were performed as described previously (Roslan et al ., 2014) at defined time points stated in figure legends. Viable cell were counted by trypan blue dye exclusion at indicated time points stated in figure legends.…”
Section: Methodsmentioning
confidence: 99%
“…MTT assays were performed as described previously (Roslan et al ., 2014) at defined time points stated in figure legends. Viable cell were counted by trypan blue dye exclusion at indicated time points stated in figure legends.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether these phenotypes were confined to 3T3 cells, we examined a second stable TPD52-expressing cell line, derived from the breast cancer cell line MDA-MB-231 with low endogenous TPD52 expression levels (Roslan et al, 2014). Again, increased lipid droplets were detected in TPD52-transfected MDA-MB-231 cells (TPD52-H1D2) compared to vector control cells (supplementary material Fig.…”
Section: Stable Tpd52 Expression Increased Cellular Lipid Droplet Nummentioning
confidence: 99%
“…Increased fatty acid synthase (FASN) expression has been noted in response to exogenous ERBB2 expression in breast cancer cells (Kumar-Sinha et al, 2003), and genes encoding other regulators of lipid metabolism might be coamplified with ERBB2 at chromosome 17q (Kourtidis et al, 2010). TPD52 expression has been reproducibly associated with ERBB2 expression in human breast cancer cell lines and tissues, and in mammary tissues from Erbb2 transgenic mice Kourtidis et al, 2010;Roslan et al, 2014). By contrast, knockdown of the Caenorhabditis elegans TPD52 orthologue F13E6.1 significantly reduces lipid storage as assessed by a genome-wide screening study (Ashrafi et al, 2003), and expression microarray analyses have identified increases in TPD52 levels in mouse and human adipose tissue from obese versus lean subjects (Clement et al, 2004;Keller et al, 2008;Nadler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…21 At the time, we were analyzing the effects of TPD52 knock-down in breast cell lines. 22 Like Kourtidis et al, 21 we noted that TPD52 knock-down decreased the survival of ERBB2-positive breast cancer cell lines, 22 which were characterized by higher levels of LD staining. 21 Breast and prostate cancers have been shown to accumulate cytoplasmic LDs, [23][24][25] and ERBB2 expression in breast cancer has been associated with a transcriptional program upregulating fatty acid synthase.…”
Section: Early Evidencementioning
confidence: 49%
“…10 There is therefore no shortage of explanations for why cancer cells might benefit from TPD52 overexpression, but these explanations are relatively generic and would not be expected to favor one cancer cell type over others. Where knock-down studies have been conducted in different breast cell lines, reduced TPD52 expression commonly reduced the survival of ERBB2-positive breast cancer cell lines, 21,22 suggesting a particular function in this cell type. ERBB2-positive breast cancer cell lines are characterized by increased LDs, 21 and ERBB2-positive breast cancers more frequently express proteins associated with lipogenesis or lipid storage.…”
Section: Lipid Droplets and Cancermentioning
confidence: 99%